Risk Stratification Model for Predicting the Overall Survival of Elderly Triple-Negative Breast Cancer Patients: A Population-Based Study - Liu, Xiaozhu; Yue, Song; Huang, Haodong; Duan, Minjie; Zhao, Binyi; Liu, Jin; Xiang, Tianyu (Frontiers in Medicine, 2021)
Background: The purpose of this study was to evaluate the prognostic value of clinical characteristics in elderly patients with TNBC. Methods: The cohort was selected from Surveillance, Epidemiology, and End Results (SEER) program dating from 2010 to 2015. Univariate and multivariate analyses were performed using Cox proportional risk regression model, and a nomogram was constructed to predict the 1-, 3- and 5- year prognosis of elderly patients with TNBC. Conformance index (C-Index), calibration curve and decision curve analysis (DCA) were used to verify the Nomogram. The results: We identified a total of 5677 patients, who were randomly divided 6:4 into a training set (n=3422) and a validation set (n=2255). Multivariate analysis showed that age, race, grade, TN stage, marital status, chemotherapy status, radiotherapy status, and tumor size at diagnosis were independent factors affecting the prognosis of elderly TNBC patients. Together, the 1 -, 3 -, and 5-year nomograms were made up by 8 variables. The C-index of the training set and validation set were 0.757 (95%CI 0.743-0.772) and 0.750 (95%CI 0.742-0.768), respectively. The calibration curve showed that the actual observation of OS was in good agreement with the prediction of the Nomogram. DCA showed that the Nomogram had good clinical application value. According to the score of each patient, the risk stratification system of elderly TNBC patients was further established, and the elderly TNBC patients were perfectly divided into three groups of low risk, medium risk and high risk in all queues. In addition, the results showed that Radiotherapy improved prognosis in the low-risk group (P =0.00056), but has no significant effect in the medium-risk group (P<0.4) and high-risk group (P<0.71). An online APP was built based on the proposed nomogram for convenient clinical use. Conclusion: This study is the first to construct a nomogram and risk stratification system for elderly TNBC patients, the well-established nomogram and the important findings from our study will guide follow-up management strategies for patients with TNBC in the elderly and help clinicians to improve individual treatment.